Impact of smoking‐induced dysregulated human miRNAs in chronic disease development and their potential use in prognostic and therapeutic purposes. Issue 9 (13th June 2022) - Paul, Sujay; Ruiz‐Manriquez, Luis M.; Ambriz‐Gonzalez, Hector; Medina‐Gomez, Daniel; Valenzuela‐Coronado, Estefania; Moreno‐Gomez, Paloma; Pathak, Surajit; Chakraborty, Samik; Srivastava, Aashish
Abstract: MicroRNAs (miRNAs) are evolutionary conserved small noncoding RNA molecules with a significant ability to regulate gene expression at the posttranscriptional level either through translation repression or messenger RNA degradation. miRNAs are differentially expressed in various pathophysiological conditions, affecting the course of the disease by modulating several critical target genes. As the persistence of irreversible molecular changes caused by cigarette smoking is central to the pathogenesis of various chronic diseases, several studies have shown its direct correlation with the dysregulation of different miRNAs, affecting numerous essential biological processes. This review provides an insight into the current status of smoking‐induced miRNAs dysregulation in chronic diseases such as COPD, atherosclerosis, pulmonary hypertension, and different cancers and explores the diagnostic/prognostic potential of miRNA‐based biomarkers and their efficacy as therapeutic targets.